Psychiatric Sequelae Following Whiplash Injury: A Systematic Review - Al-Khazali, Haidar Muhsen; Ashina, Håkan; Iljazi, Afrim; Al-Sayegh, Zainab; Lipton, Richard B.; Ashina, Messoud; Ashina, Sait; Schytz, Henrik W. (Frontiers in Psychiatry, 2022)
Background: Anxiety, depression, post-traumatic stress disorder, and sleep disturbance are reported following whiplash injury. However, the prevalence of these condition varies among studies. In this review, anxiety, depression, PTSD, and sleep disturbance will be referred as psychiatric outcomes. Methods: We performed a systematic literature search on PubMed and Embase (from database inception until March 20, 2021) to identify studies reporting on the relative frequency of these psychiatric outcomes. Three independent investigators screened titles, abstracts and full-texts. Studies including patients with whiplash injury and where the number of patients with whiplash and anxiety, depression, PTSD, or sleep disturbances could be extrapolated, were included. Furthermore, to be included, studies had to defined psychiatric outcomes in accordance with diagnostic criteria (i.e., Diagnostic and Statistical Manual of Mental Disorders (DSM) or the International Classification of Diseases (ICD)) or by use of a validated instrument with cut-off scores for assessing psychiatric symptoms. Quality rating was done using the Newcastle-Ottawa Scale (NOS) on the included studies. A protocol was registered with PROSPERO (CRD42021232037). Results: The literature search identified 5,068 citations, of which five articles were eligible for inclusion. The relative frequency of depressive symptoms following whiplash injury was 32.8% at 6 months, and 34.0% at 6-12 months. The relative frequency of PTSD symptoms after whiplash injury was 9.0-22.3% at 3 months, 15.8% at 6 months and 14.6-17.1% at 12 months. No studies evaluating the relative frequency of anxiety and sleep disturbances were eligible for inclusion. Discussion and conclusion: Our results suggest that there are persistent psychiatric outcomes following whiplash trauma. However, we found considerable heterogeneity among the studies. Thus, we have focused on the most notable limitations of the included studies: 1) small sample sizes, 2) differences in enrollment criteria, 3) lack of control groups, 4) considerable variation in the method used for outcome assessment, 5) directionality of association is difficult to determine and 6) incomplete assessment of compensation factors. We highlight these methodological limitations and outline recommendations for future research. Since psychiatric outcomes are potentially modifiable, future studies should optimize and address the identified methodological limitations so psychiatric sequelae following whiplash injury may be prevented.